(untitled) (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1952)
This work represents an effort to a better knowledge of the behaviour of cisticercosis in bovines and swines in São Paulo and in the neighbouring States of Minas Gerais, Goiaz and Mato Grosso. The data were collected by the Federal Inspection Service from July, 1941 to June, 1952, at the Anglo Packing House, located in Barretos, State of São Paulo, Brazil.